Early Appendicectomy in Appendicular Mass- Review of Literature - Ali, Mohammad; Jahan, Kazi lsrat (Journal of Surgical Sciences, 2019)
The management of appendicular mass is a matter of controversy. Traditional management hasbeen conservative, with interval appendicectomy performed weeks after the mass had resolved.The need for interval appendicectomy (I.A) after successful conservative management of appendicularmass has recently been questioned. Furthermore, emergency appendicectomy for appendicularmass is increasingly performed with equal success and safety to that performed in nonmassforming acute appendicitis. The routine adoption of emergency appendicectomy in patientspresenting with appendicular mass obviates the need for a second admission and an operation forI.A. It also abolishes misdiagnoses and deals promptly with any unexpected ileo-cecal pathology.Early emergency appendicectomy is becoming the standard of care for appendicular mass. Journal of Surgical Sciences (2017) Vol. 21 (1) :33-35